The Effects of Global Warming on the Natural Grassland Vegetation in Japan (<Special Feature>Ecological Consideration for the Distribution of Natural Grassland Vegetation Zones in Relation to the Climate and Climate Change in Japan) - 西村, 格; 佐々木, 寛幸; 浦野, 豊; 小森谷, 祥明; 井上, 聰; 西村, 由紀 (日本草地学会, 2001)
application/pdf We predicted how natural grassland vegetation in Japan will change in response to the global warming. We divided the Japanese grassland vegetations into four vegetation zones the subarctic, the cool-temperate, the warm-temperate and the subtropical grassland vegetation zones according to Zoysia japonica-type grassland and Z. tenuifolia-type grassland, Sasa-type grassland and Pleioblastus chino-type grassland. According to our results, the distribution in natural grassland vegetation will not change within the next 50 to 60 years. After that, however, the temperature will rise so rapidly and the maximum snow depth will decrease rapidly. One hundred years from now later, the temperature will rise around 3.3 to 3.8 degrees Celsius and the natural vegetation zones in Japan will greatly change. In Hokkaido, the subarctic natural grassland vegetation zone in lowland area will disappear. And the warm-temperate natural grassland vegetation zone in the lowland will spread to Shimokita and Tsugaru peninsula, the northernmost of the mainland, and will also appear even in the plains around Abashiri and Tokachi district in Hokkaido. The cool-temperate natural grassland vegetation zone in Shikoku, Kyusyu and Kii peninsula were predicted to have mostly disappear. On the other hand, the subtropical natural grassland vegetation zones in lowlands of Kyusyu and Shikoku were predicted to spread over Boso peninsula, the south part of Kanto, and the southern Izu peninsula. Article journal article